If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c(w + -5) = 0 Reorder the terms: c(-5 + w) = 0 (-5 * c + w * c) = 0 (-5c + cw) = 0 Solving -5c + cw = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'c'. c(-5 + w) = 0Subproblem 1
Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0Subproblem 2
Set the factor '(-5 + w)' equal to zero and attempt to solve: Simplifying -5 + w = 0 Solving -5 + w = 0 Move all terms containing c to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + w = 0 + 5 Combine like terms: -5 + 5 = 0 0 + w = 0 + 5 w = 0 + 5 Combine like terms: 0 + 5 = 5 w = 5 Add '-1w' to each side of the equation. w + -1w = 5 + -1w Combine like terms: w + -1w = 0 0 = 5 + -1w Simplifying 0 = 5 + -1w The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
c = {0}
| 0.02p+0.07(1200-p)=70 | | -2(6m+7)= | | 8x^3-62x^2+43x-7=0 | | 7c-6=8c-11 | | (-3x+5)+(-8x+30)=90 | | 20x^3-25x=0 | | 2-4x=-2x+4 | | Log(7)0= | | 3(3+4x)=21 | | 42-8x=14+6x | | 108=-2(2+8v) | | 11x+9x=140 | | -9+-8(-9q+-8)= | | 7t-2t=20-4+9 | | -3x-6+9x=-4x+6 | | 4k+1+3k=-6 | | 6(2x+10)=72 | | 1.75+0.35=2.80 | | 3(1-2x)=-5(3x-2) | | 8x-4=19-3x | | 2(w+5)+2w=70 | | V=imh | | -3(x-6)=-3-3x | | 2(4v-6)-2v=-8+5v | | 4y-3y-1=8 | | 2x-8=2(x-5) | | 2(3x+5)+2(8)=112 | | 0.25p=30 | | -5=-7(x+3)-3x | | 91-(6x+15)=6(x+4)+x | | 7x+17-5x+17=6 | | 21-8=x |